DIRECT REDUCTIONS IN BLOOD PRESSURE AND NOREPINEPHRINE LEVELS AFTER RENAL DENERVATION OF THE COLLECTING SYSTEM. (April 2021) - Hering, Dagmara; Hubbard, Brad; Heuser, Richard
Abstract : Objective: Variability in both renal arterial anatomy and distribution of peri-arterial renal efferent and afferent nerves affect the magnitude of blood pressure (BP) response to arterial renal denervation (RDN). No useful markers of procedural success for RDN have yet been identified. This study was performed to examine the effectiveness of RDN of the renal pelvis nerves on BP, norepinephrine (NE) and histopathology of the treated zone in a porcine model. Design and method: A total of 74 porcine kidneys obtained from female swine (3.5–5 months old) weighting 60–65 kg underwent bilateral RDN via ureteral access with the catheter-based 4-electode VERVE Medical PhoenixTM system positioned in the renal pelvis. Renal cortical tissue was harvested and NE levels were measured using HPLC directly post procedure and 7, 14, 30 and 90 days after RDN. Intraarterial BP was measured directly throughout RDN and at 14 days follow-up. Pyelograms, direct visual evidence of RDN with ureteroscopy, gross examination and histopathology of the kidneys, and ureters were also performed. Results: Using a baseline of 600 ng/g (controls), the porcine kidneys had a mean NE concentration reduction of 76% directly post procedure, 60% at 7 days, 60% at 14 days, 57% at 30 days and 65% at 90 days follow-up. There was an immediate fall in BP for systolic of -20.6 ± 20.5 and diastolic of -6.0 ± 9.3 mmHg during ablation of the renal pelvis which was maintained at follow-up. Histopathological results confirmed nerve ablation of the treated zone with unremarkable kidney, ureter, and peripelvic nerves peripheral to the immediate treatment sites. Pyelograms of renal pelvis showed no remodeling in the renal pelvis related to the device. Conclusions: The immediate reduction in BP and NE accompanied by nerve damage of the treated zone suggest a successful ablation of abundance of efferent and afferent nerves residing in the collecting system, providing an encouraging target for RDN. If VERVE clinical studies confirm efficacy and safety, this approach can be widely used for the treatment of hypertension, and alternative therapy for patients with renal artery abnormalities and anatomical ineligibility for arterial approach.